Short-term histological evaluations after achieving a sustained virologic response to direct-acting antiviral treatment for chronic hepatitis C. Issue 9 (November 2018) - Enomoto, Masaru; Ikura, Yoshihiro; Tamori, Akihiro; Kozuka, Ritsuzo; Motoyama, Hiroyuki; Kawamura, Etsushi; Hagihara, Atsushi; Fujii, Hideki; Uchida-Kobayashi, Sawako; Morikawa, Hiroyasu; Murakami, Yoshiki; Kawada, Norifumi
Background: Interferon-free, direct-acting antiviral treatments can result in a sustained virologic response in nearly 100% of patients with chronic hepatitis C virus infection. Aims: The purpose of this study was to evaluate histological improvement after achieving a sustained virologic response to direct-acting antiviral treatments in patients with chronic hepatitis C. Methods: Among 691 patients with chronic hepatitis C who achieved a sustained virologic response to direct-acting antivirals, 51 underwent liver biopsy 41 ± 20 weeks after the end of treatment despite normal transaminase levels. In 20 patients, liver biopsy specimens obtained a median of 1.2 years before the start of treatment were available. Results: Among the 51 patients who underwent post-sustained virologic response biopsies, the grade of inflammation was A0 in 18 patients, A1 in 24, A2 in eight, and A3 in one; the stage of fibrosis was F0 in three patients, F1 in 20, F2 in 15, F3 in nine, and F4 in four. Among the nine post-sustained virologic response biopsy specimens with moderate-to-severe inflammation (≥A2), four showed S1-to-S3 steatosis (>5% of hepatocytes affected). In the 20 paired biopsy specimens, the inflammation grade significantly regressed ( p  = 0.0043), but the fibrosis stage did not ( p  = 0.45). Histological improvement, defined as a ≥ 2-point decrease in the Knodell inflammatory score and no worsening of the fibrosis, was found in 11 (55%) patients. The iron accumulation had significantly regressed ( p  = 0.0093), but the steatosis had not ( p  = 0.10). Conclusions: Even if transaminases become normal after obtaining a sustained virologic response, significant histological inflammation of unknown cause was found in some patients. Additionally, improvement in liver fibrosis was not evident in the short term.